The Relationship between the Tutor's Andragogy Approach and the Activeness of Package C Learners at PKBM Uhibbu Ummi Kab. Lima Puluh Kota - Dina, Rahma; Natsir, MHD (Universitas Negeri Padang, 2024)
This study is motivated by the low learning activity of the learning communities in participating in the learning process of the PKBM Uhibbu Ummi Kab. Lima Puluh Kota. Researchers suspect that the cause of the low learning activity in learning communities may be due to the lack of application of the andragogic approach by tutors. The purpose of this study is to provide an overview of the use of andragogic approaches, descriptions of active learning, and the relationship between the two. This type of study is a correlative descriptive quantitative research. The research population was students of class XI and XII Package C who met the criteria of 37 people and the entire population was used as respondents. The data collection technique is survey-based using survey-based data collection tools. The data analysis method in this study uses the formula for percent and product moments. Results of this study indicate that: (1) the use of the tutor's andragogy approach is still low, (2) community learning activities are still low, and (3) there is a significant relationship between the tutor's andragogy approach and the learning activities of Package C residents at PKBM Uhibbu Ummi Kab. Lima Puluh Kota.